Diversity Gen Growth Hormone (Gh) of Kacang Goat In Kota Gorontalo and Regency Of Bone Bolango (Province Of Gorontalo) - Ilham, Fahrul; Safriyanto Dako, Safriyanto; Rachman, Agus Bahar; Dagong, Muhammad Ihsan Andi; Rahim, Lellah (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
ABSTRACT Growth Hormone (GH) is a hormone produced by cells in the anterior lobe of the pituitarysomatrotop and formation process under the control of GH gene. One important function of thishormone is to help the process of tissue formation and metabolism of fat to meat forming. Thepurpose of this study was to determine the genetic diversity of genes GH Kacang goat in subpopulations of Kota Gorontalo and Regency of Bone Bolango. Blood samples were used for DNAextraction process in Centre of Biotechnology Laboratory University of Hasanuddin is 41 samples ofKacang goats with 21 samples from Kota Gorontalo city and 20 samples from Regency of BoneBolango. Genomic DNA was extracted using a kit DNA extraction Genjet Genomic DNA Extraction(Thermo Scientific) following standard protocol phenol-chloroform, amplified by the technique ofPolymerase Chain Reaction (PCR), and genotyping was done by Polymerase Chain ReactionRestrictionFragment Length Polymorphism (PCR-RFLP) using the restriction enzyme Hae III. Datawere analyzed descriptively by calculating the frequency of genotype, allele frequency, and degreeof heterozygosity. The results showed GH genotype frequencies for the genotypes AA and  AB were2.45 and 97.5% respectively and the frequency of alleles A and B were  51.2 and 48.7% per centrespectively and the observed heterozygosity (Ho) and expected heterozygosity (He) were 0.97 and0.50 respectively. Based on the sub-population genotype frequencies obtained GH gene of Kacanggoat from Kota Gorontalo is 95.25 % for  AA and 4.76% for AB, the frequency of allele A and B was52.3% 47.6%, observated heterozygosity (Ho) 0.95 and expected heterozygosity (He ) 0.51. GH genegenotype frequencies in Kacang goat from Regency of Bone Bolango is AB 100%, the frequency ofallele A and allele B 0.5 0.5, observation heterozygosity (Ho) of 1.00 and expectation heterozygosity(He) 0.51. Based on the results concluded GH gene Kacang goat from Kota Gorontalo and Regency ofBone Bolango is polymorphic so that it can be used as the basis for the implementation of theselection.Key Words: Genetic Diversity, Growth Hormone, Kacang Goat